Epimedin C alleviated osteoarthritis development by regulating chondrocyte Nrf2-mediated NLRP3 inflammasome axis - Changchang Liu; Guangyu Duan; Shengjie Xu; Teng Li; Xin Sun (Heliyon)
Osteoarthritis (OA) is a prevalent musculoskeletal disorder globally. This study explored the therapeutic potential of Epimedin C (Epi C) in OA and its mechanisms. We isolated primary chondrocytes from mice and induced inflammatory damage using interleukin-1β (IL-1β) to evaluate Epi C's capacity to preserve cell viability and inhibit apoptosis, employing cell counting kit (CCK8) assays, EdU staining, and flow cytometry. Additionally, its anti-inflammatory effects were quantified using enzyme-linked immunosorbent assay (ELISA), Western blot, and real-time fluorescence quantitative polymerase chain reaction (RT-qPCR), alongside assessments of extracellular matrix (ECM) degradation. In vivo, OA was induced in mice through destabilization of the medial meniscus (DMM), followed by Epi C administration. Cartilage integrity was evaluated via micro-computed tomography (CT) and histology. Nuclear factor erythroid 2-related factor 2 (Nrf2) pathway involvement was investigated through siRNA knockdown and oxidative stress markers, while NOD-like receptor thermal protein domain associated protein 3 (NLRP3) inflammasome expression was measured to establish Epi C's modulatory effect. Our study revealed that Epi C protected against IL-1β-induced chondrocyte damage by enhancing cell viability, reducing apoptosis, and dampening inflammatory responses. The in vivo studies demonstrated Epi C's role in preserving cartilage structure, activating nuclear factor erythroid 2-related factor 2 (Nrf2), and inhibiting NLRP3 expression in DMM-induced OA mice. Conclusively, our findings provide substantial evidence of Epi C's therapeutic efficacy in OA, primarily through its modulation of the Nrf2-mediated NLRP3 inflammasome pathway, offering novel insights into its management role in OA.